Genetic analysis of some yield and quality traits in bread wheat (Triticum aestivum L.) - Arya, Vichitra Kumar; Kumar, Pradeep; Singh, Jogendra; Kumar, Lokendra; Sharma, Amit Kumar (Journal of Cereal Research, 2018)
Forty-five crosses derived from 10 diverse genotypes using diallel fashion were evaluated in 3-RBD for combining ability. Significant differences among treatments, parents, crosses, and parent vs crosses were observed for all the traits studied. The results from the present study revealed that three parents viz., K 612, HUW 648 and WCW 95-1 were found to be good general combiners due to their high general combining ability effect. Cross combinations namely; K 612/K 910-4; K 612/WCW 95-1; K 612/NW 4081; K 612/NW 4035; HUW 648/AAI 13; HUW 648/HUW 658; HUW 648/K 307; HUW 648/K 910-30; AAI13/ K 910-30, K 910-4/NW 4081; HUW 658/K 307; HUW 658/K 910-30; K 307/NW 4035; WCW 95-1/NW 4035 showed desired specific combining ability effect for grain yield along with some attributing traits. Thus, the present study suggests that these cross combinations may be utilized in the development of high yielding genotypes with desirable traits for improving the bread wheat. Doi.org/10.25174/2249-4065/2018/72641